The Politics of Power: Ridwan Kamil and the Dynamics of the 2024 Jakarta Election - Bangun, Immanuel Cristwo (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2025)
The 2024 Jakarta elections reflect the complexity of politics in Indonesia, where power is used strategically to maintain dominance. This paper aims to analyse the dynamics of power used by Ridwan Kamil, through the approach of Steven Lukes' (2005) three-dimensional view of power. Using a qualitative descriptive method based on literature study, this paper finds that although Ridwan Kamil utilizes the dimensions of Visible, Hidden and Invisible Power strategically; public resistance hinders the effectiveness of this strategy. This confirms that in an increasingly elitist political system, the 2024 Jakarta election still proves that as in democratic politics, power is not solely about elite dominance but also a matter of legitimacy and public acceptance that cannot be fully controlled by political actors. Although it cannot be denied that the power struggle between elites will always continue to occur.